Simple Autofluorescence-Restrictive Sorting of eGFP+ RPE Cells Allows Reliable Assessment of Targeted Retinal Gene Therapy - Alsing, Sidsel; Lindholm, Anna Bøgh; Haldrup, Jakob; Jensen, Emilie Grarup; Mikkelsen, Jacob Giehm; Aagaard, Lars; Askou, Anne Louise; Corydon, Thomas (Frontiers in Drug Delivery, 2022)
Gene therapy is a promising therapeutic modality for ocular diseases arising in and affecting the retina and choroid. In this context, delivering gene therapy to the multifunctional retinal pigment epithelium (RPE) cells situated between the retina and choroid is desired. Efficacy assessment of any gene therapy strategy, whether it is gene augmentation, inhibition, or editing is initially tested in vitro in cell models, where delivery is simple and efficient. However, efficacy assessment in vivo in animal models is far more complex and several factors can influence the result significantly. Here we report a simplified fluorescence activated cell sorting (FACS)-based enrichment method for direct assessment of efficacy and potential off-target effects of gene therapy co-delivered with an eGFP reporter to murine RPE cells using subretinal administration. Isolation of true eGFP+ RPE cells by FACS is notoriously difficult due to their intrinsic autofluorescence resulting in decreased sensitivity and false positives. Combining retinal dissection and harvest of RPE cells with a FACS-gating strategy utilizing the GFP filter and a neighboring filter, to separate the eGFP signal from autofluorescence, allows a significant enrichment of gene therapy targeted eGFP+ RPE cells. The isolated cells can subsequently be utilized for reliable assessment of changes in DNA, RNA, or protein. This method allows proof of principle analysis of early gene therapy development and investigation of new delivery strategies or therapeutic approaches targeting RPE cells in vivo.